A simplified method to assess seismic behavior of reinforced concrete columns. (8th September 2019) - Wang, Zhen; Wang, Jingquan; Zhu, Junzheng; Zhang, Jian
Abstract: A simplified method was proposed to assess the seismic behavior of reinforced concrete columns that failed in different modes. In this method, an analytical monotonic model was established to obtain lateral force‐displacement curves, and the Ibarra–Medina–Krawinkler model was utilized to simulate hysteretic behavior. For the Ibarra–Medina–Krawinkler model, the backbone curve was determined based on the proposed monotonic model, and the two parameters κ and γ ed used to describe pinching effect and deterioration, respectively, were calculated with two suggested regression formulas. The nonlinear pushover and dynamic analyses were conducted based on the proposed method. The obtained results were compared with the results of cyclic loading and shake table tests on reinforced concrete columns that failed in different modes. Results show that the proposed monotonic model adequately captures not only the prepeak response but also the postpeak branch. The parameters κ and γ ed are approximately linear to the longitudinal reinforcement ratio and the shear span ratio. For the two parameters, the proposed regression formulas can provide closer predictions to the experimental calibrations. The Ibarra–Medina–Krawinkler model determined with the proposed method can be used to assess the dynamic response of reinforced concrete columns with or without sufficient stirrups.